Feedback to EFL learners’ writing: An investigation of teachers and students’ perceptions at a Saudi University - Alharbi, Bader (Linguistics and Culture Review, 2021)
Teachers’ feedback is the backbone of students’ learning experience and one that helps them stem their errors early. At the same time, the perceptions of teachers and learners to the role of feedback in second language skills is central to developing healthy classroom practices. This is also the aim of this study which investigates the perceptions of teachers and students to feedback to writing output in an EFL environment in a Saudi University. The study sample comprises 35 students and 5 teachers at Qassim University, Saudi Arabia. The study uses questionnaires and supplementary interviews in a field survey to obtain the data. The findings show that both students and teachers have a positive perception to written feedback, espousing it as a fundamental instructional delivery tool in EFL pedagogy that improves learning outcomes. Moreover, the majority of the participants report that written feedback positively influences learning outcomes through correction of grammar in students’ writing. Similarly, the study shows that teachers depend on different mechanisms to select the nature of feedback as well as the interest of students and curricular instructions.